2007
DOI: 10.1051/0004-6361:20066442
|View full text |Cite
|
Sign up to set email alerts
|

Gas stripping in galaxy clusters: a new SPH simulation approach

Abstract: Aims. The influence of a time-varying ram pressure on spiral galaxies in clusters is explored with a new simulation method based on the N-body SPH/tree code GADGET. Methods. We have adapted the code to describe the interaction of two different gas phases, the diffuse hot intracluster medium (ICM) and the denser and colder interstellar medium (ISM). Both the ICM and ISM components are introduced as SPH particles. As a galaxy arrives on a highly radial orbit from outskirts to cluster center, it crosses the ICM d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 27 publications
4
91
1
Order By: Relevance
“…In Jáchym et al (2007) for an example the stripped ISM does not show clumps of cool gas. In the eulerian grid simulations of Roediger et al (2006) the wake does show cooler, dense regions, but the number is much less as in the simulations presented here.…”
Section: Comparison To Other Simulations Of Ram-pressure Strippingmentioning
confidence: 99%
“…In Jáchym et al (2007) for an example the stripped ISM does not show clumps of cool gas. In the eulerian grid simulations of Roediger et al (2006) the wake does show cooler, dense regions, but the number is much less as in the simulations presented here.…”
Section: Comparison To Other Simulations Of Ram-pressure Strippingmentioning
confidence: 99%
“…The buildup of HI and enhancement of radio continuum emission in NGC 1961's southeastern ridge could then be accounted for by an edge-on stripping geometry. For such a geometry, simulations predict that a galaxy encountering an intragroup medium for the first time should have its H I extended on the side where the galactic rotation adds to the velocity relative to the IGM and the gas is more stripped on the other side (see the explanation of this paradox in Roediger & Brüggen 2006;Jachym et al 2007Jachym et al , 2009). For NGC 1961, which is falling into its group from the northwest, we see an extended H I structure on the northern side of the galaxy, coming from the west (Haan et al 2008).…”
Section: A Possible Minor Mergermentioning
confidence: 99%
“…Numerical modeling has shown that ram pressure stripping is a very efficient process for removing the gaseous content of cluster galaxies (e.g., Vollmer et al 2001;Roediger & Hensler 2005;Jáchym et al 2007Jáchym et al , 2009. Simulations also predict that material IC3418 M87 M86 0.5 deg Fig.…”
Section: Introductionmentioning
confidence: 95%